PERAN GURU DALAM MANAJEMEN KELAS UNTUK PENINGKATAN KECERDASAN EMOSIONAL - Fitrianik, A. Busyairi, Cahya (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2019)
This research aimed to describe the role of teachers in class management to improve the emotional intelligence of the fifth grade students at Purwoyoso 06 Elementary School Semarang. This research was descriptive qualitative. The subjects of the research is 1 teacher and 41 students of the fifth grade at Purwoyoso 06 Elementary School Semarang. The data collection techniques used were interviews, observations, questionnaires, documentation and field notes. The data analysis techniques used Miles and Huberman. The results of this study were: 1) The role of the teacher was very good starting from educators, instructors, role models, advisers, class managers, and evaluators. 2) The classroom management conducted by the teacher included 4 proces management class from thebeginning to the end of the activities both in term of preventive and corrective have been designed to the maximum. 3) Increased emotional intelligence of students is characterized by good emotional characteristics . The conclusion from this research is the teacher's role was to provide direction and input as well as good examples and manage the class as best as to support students' emotional intelligence.